2006
DOI: 10.1016/j.ijpsycho.2005.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Emotional arousal in agenesis of the corpus callosum

Abstract: While the processing of verbal and psychophysiological indices of emotional arousal have been investigated extensively in relation to the left and right cerebral hemispheres, it remains poorly understood how both hemispheres normally function together to generate emotional responses to stimuli. Drawing on a unique sample of nine high-functioning subjects with complete agenesis of the corpus callosum (AgCC), we investigated this issue using standardized emotional visual stimuli. Compared to healthy controls, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 62 publications
7
30
0
Order By: Relevance
“…For example, Paul et al (2006) observed that ratings of facial-emotion valence (happy/sad) and degree of arousal (excited/calm) by patients with agenesis of the corpus callosum (AgCC) were highly inconsistent (many completely inaccurate), observing particular difficulty with negative emotions. AgCC also tended to provide lower than normal assessments of arousal.…”
Section: Rh and Lh Disconnectionmentioning
confidence: 99%
“…For example, Paul et al (2006) observed that ratings of facial-emotion valence (happy/sad) and degree of arousal (excited/calm) by patients with agenesis of the corpus callosum (AgCC) were highly inconsistent (many completely inaccurate), observing particular difficulty with negative emotions. AgCC also tended to provide lower than normal assessments of arousal.…”
Section: Rh and Lh Disconnectionmentioning
confidence: 99%
“…Studies comparing healthy individuals with those presenting the agCC found that highly functioning agCC patients have trouble processing emotional information (e.g., interpreting correctly the arousal generated by emotional stimuli; Paul et al, 2006) or a marked deficit in processing social information (Brown and Paul, 2000; Symington et al, 2011). In addition, a review of studies with agCC and autism spectrum disorder (ASD) subjects suggests that the theory-of-mind and emotion-processing deficits in agCC are similar to those observed in ASD (Booth et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these advances, the functional consequences stemming from these morphological differences in CC have not been systematically explored. Given the evidence that agCC was found to be associated with deficits in emotion recognition, labeling of emotional arousal, and decoding visual social cues even in highly functioning and otherwise healthy individuals (Paul et al, 2006; Symington et al, 2011), it is conceivable that callosal dysgenesis in schizophrenia may also be associated with dysfunction in the treatment of emotionally laden information. Two case studies of patients with schizophrenia and agCC provided such evidence (Hallak et al, 2007; Micoulaud-Franchi et al, 2011), but a direct comparison between these kind of individuals and schizophrenia patients with no evidence of callosal abnormality has not been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…This idea stems from its global role in the integration of activity and information between the two hemispheres, and transfer of important sensory and higherorder stimuli. Much of the evidence for this has come from other populations with known callosal abnormalities, such as those with autism and callosal agenesis, as both groups have significant deficits in social interaction, recognition of emotions, comprehending humor and socially complex scenarios, detecting changes in prosody, and in social intelligence more generally (Badaruddin et al, 2007;Boger-Megiddo et al, 2006;Brambilla et al, 2003;Brown et al, 2005;Hrdlicka, 2008;Paul et al, 2007;Paul et al, 2006;Paul et al, 2004;Schmitz and Rezaie, 2008). In addition, a recent study in children with TBI indicated a marginal relationship between the presence of callosal lesions and poor performance on a social problemsolving task .…”
mentioning
confidence: 99%